2022
DOI: 10.1121/10.0010528
|View full text |Cite
|
Sign up to set email alerts
|

Accurate prediction of transmission through a lensed row-column addressed array

Abstract: Using a diverging lens on a row-column array (RCA) can increase the size of its volumetric image and thus significantly improve its clinical value. Here, a ray tracing method is presented to predict the position of the transmitted wave so that it can be used to make beamformed images. The usable transmitted field-of-view (FOV) is evaluated for a lensed 128 + 128 element RCA by comparing the theoretic prediction of the emitted wavefront position with three-dimensional (3D) finite element simulation of the emitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The amount of divergence is quantified by the FOV, which describes the angular spread of energy in the imaging medium. The thin lens model provides a simple estimation of the FOV of a lensed array based on the paraxial condition assumption but disregards the thickness and losses introduced by the lens [20]. The FOV is given by [19]:…”
Section: Designmentioning
confidence: 99%
“…The amount of divergence is quantified by the FOV, which describes the angular spread of energy in the imaging medium. The thin lens model provides a simple estimation of the FOV of a lensed array based on the paraxial condition assumption but disregards the thickness and losses introduced by the lens [20]. The FOV is given by [19]:…”
Section: Designmentioning
confidence: 99%
“…The current equations in the lensed beamformer give reasonable results, but it has been shown that ray tracing theory can further enhance the quality of the results and increase the field-of-view [62]. This should be further investigated and incorporated in the beamformers.…”
Section: B Lensed Row-column Imagingmentioning
confidence: 99%